Adaptation of the SCS [Soil Conservation Service] runoff equation for a (Sub) humid monsoon climate - Yilak, Debebe L.; Tilahun, Seifu A.; Schmitter, Petra S.; Nakawuka, Prossie; Haile, Alemseged Tamiru; Kassawmar, N. T.; Guzmán, Christian D.; Steenhuis, Tammo S. (2015)
The Soil Conservation Service Runoff equation was developed and tested for the temperate climate in the United States. Application to the monsoon climates has been only partially successful. The objective to adapt the SCS equation to a monsoon climate equation is to predict watershed runoff. The adaptation is based on the fact that in many humid areas the main mechanism for direct runoff is saturation excess and in monsoon climates the contributing area expands as a function of the cumulative effective rainfall ( Pe). This then translate in smaller watershed storage (S) in the equation. When estimating runoff contributing area within a watershed and assessing the runoff mechanisms, we have used the original concept of SCS-CN approach in a 113 ha Anjeni and 113ha Maybar Watersheds in the headwaters of the Blue Nile Basin, North Ethiopian highland. Analysis was done at daily, weekly and biweekly base using nine years of hydrological data (1988-97) by classifying the rainfall seasons in to six based on the seasonal cumulative of effective rainfall (Pe). The initial abstraction (Ia) was taken to be equal to the evapotranspiration loss (E) computed by Thornthwaite-Mather water balance method in replacement of the 20% of the potential storage (S). Effective rainfall (Pe) is the difference of total rainfall and Ia. The model performed more as the seasonal cumulative Pe is increased indicating that runoff responses occurred as the watershed saturated. The proportion of runoff contributing area (Af) increased linearly until the cumulative Pe up to nearly 500mm and then the watershed reaches in equilibrium for addition increase of Pe, which is in line with the concept of partial source area hydrology.